A class of deterministic external problems equivalent to stochastic external problems in the reliability theory of mechanical systems - Nguyen Van Pho (Vietnam Journal of Mechanics)
In this paper, the reliability of the Mechanic Systems is expressed under a new form. Then we propose au iterative method of computing of the  Reliability, and apply the obtained results to the some problems of Solid Mechanics.